Key account management: towards a multidimensional definition - Ahmmed, Kawsar; Mohd Noor, Nor Azila (KODISA, 2012)
The aim of this paper is to propose an integrative definition of key account management (KAM) at the organizational level through a content analysis of the existing definitions of KAM available in the business literatures.A representative pool of definitions of key account management was generated through literature review from twenty three journals that covers the divergence of name variety like global account management, strategic account management, national account management, international key account management, key client management, major account management, key customers management and key account management. Relating to the definition of key account management various attributes are identified through content analysis and according to the relevance, profile for each attributes are developed. On the basis of these attributes a diagrammatic and textual definition is proposed that covers the different standpoints and aspects of key account management approach and captures its essence as well.Eventually, several strategic implications are derived that create the field for further empirical investigation.